EFEKTIFITAS PEMBELAJARAN DIFERENSIASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 2 SDN BANGETAYU WETAN 02 - Mega Trisyandi; Nuhyal Ulia (STKIP Subang, 2025)
This abstract describes the research on the influence of differentiated instruction in mathematics for grade 2 student SDN Bangetayu Wetan 02. This study aimsto determine whether there is a significant difference in mathematics learning outcomes of student taugh using differentiated instruction compared to students taught using conventional methods. The research method used was a quasi- experiment with a pretest-posttest control group design. The result of the study indicate that there is a positive influence of differentiated instruction on the mathematics learning outcomes of grade 2 student.